Replication of GWAS significant loci in a sub-Saharan African Cohort with early childhood caries: a pilot study - Olubukola O. Olatosi; Mary Li; Azeez A. Alade; Afolabi Oyapero; Tamara Busch; John Pape; Joy Olotu; Waheed Awotoye; Mohaned Hassan; Chinyere Adeleke; Wasiu L. Adeyemo; Elizabeth O. Sote; et al. (BMC, 2021)
Abstract Background Early childhood caries (ECC) is a rapidly progressing form of dental infection and a significant public health problem, especially among socially and economically disadvantaged populations. This study aimed to assess the risk factors for ECC among a cohort of Sub-Saharan African children and to determine the role of genetics in the etiology of ECC. Methods A sample of 691 children (338 with ECC, 353 without ECC, age < 6 years) was recruited from schools in Lagos, Nigeria. Socio-demographic, dental services utilization and infant dietary data were obtained with interviewer-administered questionnaire. Oral examination was conducted using the WHO oral health diagnostic criteria. Saliva samples were collected from the children for genetic analysis. Single nucleotide polymorphisms were selected from previous study for genotyping. Genetic association analyses to investigate the role of genetics in the etiology of ECC was done. Bivariate comparisons and Multivariate logistic regression analyses were conducted to assess associations between ECC and predictor variables, p < 0.05. Results Of the 338 children with ECC, 64 (18.9%) had Severe-Early Childhood Caries (S-ECC). Children aged 48-59 months comprised the highest proportion of subjects with ECC (165; 48.8%) and S-ECC (24; 37.5%) while female subjects had higher dt (3.13 ± 2.56) and dmft values 3.27 ± 2.64. ECC was significantly more prevalent among children who were breastfed at night ≥ 12 months (OR 3.30; CI 0.39, 4.75), those with no previous dental visit (OR 1.71; CI 0.24, 2.77), those who used sweetened pacifiers (OR 1.85; CI 0.91, 3.79) and those who daily consumed sugar-sweetened drinks/snacks (OR 1.35; CI 0.09, 18.51). A suggestive increased risk for ECC (OR 1.26, p = 0. 0.0397) was observed for the genetic variant rs11239282 on chromosome 10. We also observed a suggestive reduced risk for ECC (OR 0.80, p = 0.03) for the rs131777 on chromosome 22. None of the genetic variants were significant after correction for multiple testing (Bonferroni p value p = 0.004). Conclusions Prolonged night-time breastfeeding, poor utilization of dental services and daily consumption of sugar were risk factors for ECC. Larger sample size is needed to confirm the results of the genetic analysis and to conduct genome wide studies in order to discover new risk loci for ECC.